Fat as an energy supplement for preterm infants. Issue 7 (July 1982) - Hanmer, O J; Houlsby, W T; Thom, H; Ross, I S; Lloyd, D J; Russell, G
Abstract : The absorption and utilisation of dietary fat as an energy supplement was studied in 15 healthy preterm infants. They were given two formulae for periods of one week. The standard low solute feed supplied 6 g fat and 476 kJ (114 cal) per kg. The high energy feed supplied 10 g of the same fat and 623 kJ (149 cal) per kg. Fat supplementation resulted in increased absorption (significantly higher chylomicron levels) without steatorrhoea or metabolic disturbance, apparently unchanged differential absorption of fatty acids, and a significantly higher rate of weight gain (mean 25.9 +/- 4.6 compared with 20.3 +/- 4.4 g/24 h). A high energy formula prepared with supplements of complex dietary fat is therefore of potential value in ensuring the adequate nutrition and growth of preterm infants.